PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. MATAHARI DEPARTMENT STORE - CICI PERMATA SARI; WASIMAN . (JURNAL ILMIAH KOHESI, 2020)
Managing human resources in the organization needs to have a clear basis and direction, able to align and balance theperformance in the organization In this study aims to determine how the influence of Work Discipline and Work Motivation onEmployee Performance at Pt Matahari Department Store. The sample was determined using the Isaac formula with 110respondents, then tested the hypothesis with SPSS Version 22 application support. Work discipline variables were ofsignificance value of 0,000 ˂ 0.05 alpha value and 4.263 ˃ 1.982 on the t table value. Variable work motivation significancelevel 0.012 ˃ 0.05 and 2.544 ˃ from the t value of 1.982 table. Variable work discipline and work motivation simultaneouslyhave a positive and significant effect with a F table value of 22,100 ˃ 3.08 F table values, and sig ˂ of alpha with a value of0,000 ˂ 0.05.